Increasing Compressive Strength of The Red Brick with Fly Ash and Rice Husk Ash - Candra, Agata Iwan; Romadhon, Fajar; Azhari, Faiz Muhammad; Hidiyati, Evita Fitrianis (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. Red brick is a building material widely used in Indonesia as a non-structural separator wall of a building. Soil is the main material in the production of red bricks. The soil used for the main material of red brick is sandy clay soil. The advantage of red brick is that it is resistant to hot weather or fire because it has undergone the combustion process. However, new innovations are necessary for the red brick manufacturing process due to the reduced soil.  The innovation carried out in this study was adding the main material with fly ash and rice husk ash. The purpose of this study was to obtain red brick mixture fly ash and rice husks with increased compressive strength than normal red bricks.  The research method used is an experimental method with the addition of fly ash and rice husk ash by 4%, 8%, and 12% of the soil weight.  The results obtained from this study are red bricks with fly ash and rice husk ash produced the highest value in the fly ash mixture of 12% (in sample D2) content of 75.07 Kgf / cm² so as to improve the quality of conventional red bricks.